Law relating to computers and Internet - Matthan, Rahul (New Delhi, 2000)
This book seeks to analyse both the development of the jurisprudence under Western legal systems as well as the applicability of the principles laid out in those courts within the framework of the Indian legal system.
Keywords: Cyber law